Method for optimizing interface stability of protein diaphragm through electron beam irradiation
The modified protein separator is processed through electron beam irradiation technology to form a stable three-dimensional network structure, which solves the low efficiency and safety risks caused by Li dendrites in lithium-ion batteries, and significantly improves the safety and cycle life of the battery.
Patent Information
- Application Number
- CN202411943509.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
During the circulation process, traditional lithium-ion batteries cause low Coulomb efficiency and rapid attenuation of capacity due to uncontrollable Li dendrites, and Li dendrites pierce the diaphragm into the positive electrode, causing internal short circuits and thermal runaway.
The modified protein separator is processed through electron beam irradiation technology, which promotes free radical reactions in protein molecules and cross-linking and recombination between molecules, forming a stable three-dimensional network structure of protein-modified separator.
It enhances the mechanical strength of the diaphragm, electrolyte wetting and ionic conductivity, significantly improves the safety and cycle life of the battery, and reduces the risks of the battery during use.
Smart Images

Figure CN119764746A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for optimizing the interface stability of a protein diaphragm by electron beam irradiation. Background Art
[0002] As a high-efficiency rechargeable battery technology that has rapidly emerged in recent years, lithium-ion batteries play an irreplaceable role in portable electronic devices, electric vehicles and large-scale energy storage systems due to their high energy density, low self-discharge rate, no memory effect and stable discharge characteristics. However, the energy density of traditional lithium-ion battery systems is close to the theoretical upper limit and it is difficult to meet the increasing demand for energy storage. Thanks to the ultra-high theoretical capacity of the lithium (Li) negative electrode (3860mA hg -1 ), low redox potential (-3.04 V relative to standard hydrogen electrode) and relatively low mass density (0.534 g cm -3 ), lithium metal batteries (LMBs) can achieve a high energy density of more than 400Wh kg-1, showing great market potential and application value. However, during the cycle of LMBs, uncontrollable Li dendrite growth leads to low Coulombic efficiency and rapid capacity decay; in addition, Li dendrites pierce the diaphragm and invade the positive electrode, causing internal short circuits, thereby triggering thermal runaway and explosion of the battery.
[0003] Functionalized diaphragms are one of the effective means to solve the above problems. As a rising star in the field of artificial composite membranes, protein membranes have unique secondary structures and adsorption and electrostatic interactions with metal surfaces, which show significant advantages in stabilizing lithium negative electrodes. This natural polymer material not only has good biocompatibility, high strength and excellent flexibility, but has also received widespread attention in the field of materials science in recent years. For example, Fu et al. (Energy Storage Mater. 2021, 42, 22-33.) prepared high-performance protein diaphragms by optimizing the configuration of zein, which significantly improved the safety and life of lithium metal batteries. In 2020, Pu Chen et al. coated collagen on glass fiber felt to generate deionized shock in the diaphragm to promote uniform electrodeposition. Chinese patent CN114335890B discloses a polymer / amyloid-like protein material that inhibits dendrite growth and a method for preparing it. This material uses an in-situ interfacial phase transformation strategy to place a polymer separator on the surface of a mixed aqueous solution of a thiol reducing agent and amyloid-like protein to form a β-folded conformation protein-modified separator, which significantly improves the safety and life of lithium metal batteries. The above patents and research reports show that protein separators have the function of stabilizing lithium deposition. However, the intermolecular interaction between the protein functional layer and the separator reported so far is weak, and the interface stability is poor.
[0004] High-energy irradiation technology has become an important direction of green preparation and modification technology due to its high energy, strong penetration and batch processing characteristics. By treating the diaphragm material with high-energy irradiation, the polymer surface can be activated and the generation of free radicals or ions can be promoted without damaging its basic structure. This process is conducive to the grafting reaction between functional monomers or polymers and the surface of the diaphragm material, thereby improving the physical and chemical properties of the diaphragm and enhancing its application performance. For example, Gao Junna et al. (Henan Chemical Industry. 2020, 37(02): 29-32) introduced trimethylolpropane triacrylate and electron beam irradiated cross-linked polyethylene lithium battery diaphragm to improve the puncture resistance of the diaphragm. Chinese patent CN109659473A discloses a method for irradiation modification of lithium-ion battery diaphragms, which improves the wettability and porosity of the diaphragm by ultraviolet irradiation treatment. The above report fully illustrates that high-energy irradiation technology can achieve cross-linking between organic substances.
[0005] The present invention is the first to use electron beam irradiation technology to treat the modified protein membrane, triggering free radical reactions in protein molecules, promoting cross-linking and recombination between molecules, and forming a stable three-dimensional network structure of the protein modified membrane. This process not only enhances the mechanical strength, electrolyte wettability and ion conductivity of the membrane, but more importantly, increases the interfacial stability of the protein membrane, significantly improves the safety and cycle life of the battery, and shows broad prospects in applications such as electric vehicles and energy storage systems. Summary of the invention
[0006] The purpose of the present invention is to provide a method for optimizing the interfacial stability of a protein membrane by electron beam irradiation. The modified protein membrane prepared by the present invention has excellent physical and chemical stability, good electrolyte compatibility, environmental friendliness, and excellent biocompatibility, and shows broad application prospects in multiple fields such as electric vehicles, energy storage systems, portable electronic devices, aerospace, and medical equipment.
[0007] A method for optimizing the interfacial stability of a protein membrane by electron beam irradiation, wherein the raw materials consist of a main material, a degumming agent, a dissolving agent, a diluent, a polymer membrane, a self-assembly solution and a cleaning agent, and the mass percentages of the seven components are: main material: 1-5%, degumming agent: 0.2-0.5%, dissolving agent: 10-20%, diluent: 50-70%, self-assembly solution: 3-5%, and cleaning agent: 1-5%; wherein the main material is any one of wool, soy protein, bovine serum albumin, collagen, and silkworm cocoon; the degumming agent is one or two of acetic acid, citric acid, oxalic acid, sodium carbonate, sodium hydroxide, potassium carbonate, potassium hydroxide, and calcium carbonate; the dissolving agent is any one of sodium hydroxide-aqueous solution, sodium phosphate-aqueous solution, potassium hydroxide-ethanol solution, lithium bromide-methanol solution, urea-aqueous solution, calcium chloride-ethanol solution, guanidine hydrochloride-aqueous solution, and lithium chloride-dimethyl sulfoxide solution; the diluent is sodium chloride solution, One or two of phosphate buffer solution, sodium sulfate solution, deionized water, and sodium nitrate solution; the polymer membrane is any one of polyethylene, polyvinylidene fluoride, polypropylene, polybenzimidazole, polyether sulfone, polyether ether ketone, cellulose, polyacrylonitrile, polyimide, and polypropylene / polyethylene / polypropylene composite membrane; the self-assembly solution is any one of zinc sulfate solution, ammonium carbonate solution, calcium nitrate solution, sodium sulfate solution, calcium chloride solution, potassium nitrate solution, and sodium phosphate solution; the cleaning agent is one or two or three of isopropanol, acetone, ethanol, deionized water, 0.1% acetic acid solution, 0.1% citric acid solution, and 0.1% oxalic acid solution; the seven components are firstly used to prepare a protein solution, which is combined with the polymer membrane through self-assembly, and electron beam irradiation treatment is used to induce free radical reactions in protein molecules, promote crosslinking and recombination between molecules, form a stable three-dimensional network structure, and obtain an electron beam irradiation optimized protein membrane.
[0008] A method for optimizing the interfacial stability of a protein membrane by electron beam irradiation comprises the following steps:
[0009] (1) Impurity removal: Place the main material in a degumming agent and boil it at 100°C for 30 minutes to remove surface impurities and non-protein components. Then, wash the main material with distilled water and dry it for later use;
[0010] (2) Dissolution and modification: The degummed main material is placed in a dissolving agent and heated at 50-80°C for 8-10 hours to completely dissolve the main material and form a uniform protein solution;
[0011] (3) Dilution and purification: dilute the solution in step (2) to 10%-30% with a diluent, remove undissolved impurities by centrifugation, and take the supernatant for later use;
[0012] (4) Self-assembly: drip the self-assembly solution into a culture dish to form a liquid layer 8 mm deep, drip a drop of the above protein solution 1-2 cm away from the culture dish, gently cover the protein solution with a polymer membrane of appropriate size to ensure that no bubbles are generated, and maintain this state for self-assembly for 0.5-3 hours;
[0013] (5) Cleaning and drying: The self-assembled membrane is cleaned with a cleaning agent to remove surface salt and unbound protein solution, and then dried at 16-25°C;
[0014] (6) Electron beam irradiation treatment: The prepared protein membrane is subjected to electron beam irradiation treatment to further enhance its physical and chemical stability.
[0015] The sizes of the polymer membrane in step (4) are 1 cm×1 cm, 3 cm×3 cm, 5 cm×5 cm, 7.5 cm×7.5 cm, and 10 cm×10 cm.
[0016] The electron beam irradiation dose in the step (6) is 0-100 kGy.
[0017] The protein membrane has excellent physical and chemical stability and can remain stable under adverse conditions such as high temperature and high pressure.
[0018] The protein diaphragm electrolyte has good compatibility, and the internal resistance of the prepared lithium battery is reduced and the charge and discharge performance is improved.
[0019] The protein diaphragm can effectively reduce the erosion and penetration of the electrolyte to the diaphragm, thereby extending the cycle life of the battery.
[0020] The method of optimizing the interface stability of a protein membrane by electron beam irradiation of the present invention is characterized by its application in the fields of electric vehicles, energy storage systems, portable electronic devices, aerospace, medical equipment, military and defense, and renewable energy.
[0021] Compared with the prior art, the present invention has the following advantages and positive effects:
[0022] (1) Based on the high toughness and stability of the protein film, the present invention uniformly self-assembles the protein solution on the base material, which not only has excellent mechanical strength and thermal stability, so that it exhibits good high temperature resistance and pressure resistance in practical applications, but also further enhances these properties through electron beam irradiation treatment, ensuring reliability and safety in extreme environments.
[0023] (2) Based on the high hydrophilicity and ion exchange capacity of the protein membrane, the present invention uniformly self-assembles the protein solution on the base material, which not only has excellent electrolyte wettability and ion conductivity, so that it exhibits good electrolyte penetration and ion transmission capabilities in practical applications, but also improves the battery's charge and discharge efficiency and energy density.
[0024] (3) Based on the uniformity and density of the protein film, the present invention uniformly self-assembles the protein solution on the base material, which can not only effectively inhibit the growth of lithium dendrites and prevent short circuits and safety accidents caused by dendrites, but also significantly improve the safety performance of the battery and reduce the risks of the battery during use.
[0025] (4) Based on the environmental friendliness and biocompatibility of natural protein fibers, the present invention uniformly self-assembles the protein solution on the base material, which not only reduces the impact on the environment, but is also suitable for application scenarios with high environmental requirements, such as medical devices and wearable devices, ensuring the long-term stability and safety of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is an appearance diagram of the silk protein film prepared by the present invention;
[0027] Figure 2 This is an appearance diagram of a lithium iron phosphate symmetrical battery assembled using the silk protein film material prepared in the present invention as a lithium battery separator;
[0028] Figure 3 This is a charge and discharge cycle diagram of a lithium iron phosphate symmetrical battery assembled using the silk protein film material prepared in the present invention as a lithium battery separator. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the present invention is not limited by the following embodiments, which are only used to illustrate the implementation method of the present invention and cannot be used to limit the operation and operating scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are still within the scope of protection of the claims of the present invention.
[0030] Examples 1-4 and Comparative Example 1 are as follows:
[0031] plan Protein membrane materials Protein concentration Self-assembly time (h) Radiation dose (kGy) Example 1 Wool protein film 15% 2 20 Example 2 Silk protein membrane 25% 1 30 Example 3 Soy protein film 25% 1.5 50 Example 4 Silk protein membrane 20% 1 100 Example 5 BSA membrane 20% 1.5 100 Comparative Example 1 Silk protein membrane 25% 1 0
[0032] Example 1
[0033] (1) Impurity removal: Place the wool in a sodium hydroxide solution and boil it at 100°C for 30 minutes to remove the grease and non-protein components on the surface. Wash the wool with distilled water and dry it for later use.
[0034] (2) Dissolution and modification: The degummed wool is placed in a urea-water solution and heated at 70°C for 10 hours to completely dissolve the wool and form a uniform protein solution;
[0035] (3) Dilution and purification: dilute the solution in step (2) to 15% with sodium chloride solution, remove undissolved impurities by centrifugation, and take the supernatant for later use;
[0036] (4) Self-assembly: Sodium sulfate solution was dripped into a culture dish to form a liquid layer 8 mm deep. A drop of the modified protein solution was dripped 1 cm away from the culture dish. A 5 cm × 5 cm polyethylene membrane was gently covered on the protein solution to ensure that no bubbles were generated. This state was maintained for self-assembly for 2 hours.
[0037] (5) Cleaning and drying: The self-assembled membrane was cleaned with isopropanol to remove surface salt and unbound protein solution, and then dried at 22 °C;
[0038] (6) Irradiation treatment: The prepared protein membrane was subjected to electron beam irradiation treatment with an irradiation dose of 20 kGy.
[0039] Example 2
[0040] (1) Removing impurities: Place the cocoons in a sodium carbonate solution and boil them at 100°C for 30 minutes to remove sericin and other impurities on the surface. Wash the cocoons with distilled water and dry them for later use.
[0041] (2) Dissolution and modification: The degummed silk cocoons were placed in a lithium bromide-methanol solution and heated at 65°C for 8 hours to completely dissolve the cocoons and form a uniform protein solution;
[0042] (3) Dilution and purification: The solution in step (2) was diluted to 25% with deionized water, and undissolved impurities were removed by centrifugation, and the supernatant was taken for later use;
[0043] (4) Self-assembly: Add ammonium carbonate solution to a culture dish to form a liquid layer 8 mm deep, add a drop of the modified protein solution 1 cm away from the culture dish, and gently cover the protein solution with a 1 cm × 1 cm polypropylene membrane to ensure that no bubbles are generated. Maintain this state for self-assembly for 1 hour;
[0044] (5) Cleaning and drying: The self-assembled membrane was cleaned with deionized water to remove surface salt and unbound protein solution, and then dried at 20 °C;
[0045] (6) Irradiation treatment: The prepared protein membrane was subjected to electron beam irradiation treatment with an irradiation dose of 30 kGy.
[0046] Example 3
[0047] (1) Impurity removal: Place the soybean protein in a potassium carbonate solution and boil it at 100° C. for 30 minutes to remove non-protein components on the surface, wash the soybean protein with distilled water, and dry it for later use;
[0048] (2) Dissolution and modification: The degummed soy protein was placed in a calcium chloride-ethanol solution and heated at 60°C for 9 hours to completely dissolve the soy protein and form a uniform protein solution;
[0049] (3) Dilution and purification: The solution in step (2) was diluted to 25% with deionized water, and undissolved impurities were removed by centrifugation, and the supernatant was taken for later use;
[0050] (4) Self-assembly: Calcium chloride solution was dripped into a culture dish to form a liquid layer 8 mm deep. A drop of the modified protein solution was dripped 1.5 cm away from the culture dish. A 3 cm × 3 cm polypropylene membrane was gently placed on the protein solution to ensure that no bubbles were generated. This state was maintained for self-assembly for 1.5 hours.
[0051] (5) Cleaning and drying: The self-assembled membrane was cleaned with ethanol to remove surface salt and unbound protein solution, and then dried at 20 °C;
[0052] (6) Irradiation treatment: The prepared protein membrane was subjected to electron beam irradiation treatment with an irradiation dose of 50 kGy.
[0053] Example 4
[0054] (1) Removing impurities: Place the cocoons in a sodium carbonate solution and boil them at 100°C for 30 minutes to remove sericin and other impurities on the surface. Wash the cocoons with distilled water and dry them for later use.
[0055] (2) Dissolution and modification: The degummed silk cocoons were placed in a lithium bromide-methanol solution and heated at 65°C for 8 hours to completely dissolve the cocoons and form a uniform protein solution;
[0056] (3) Dilution and purification: The solution in step (2) was diluted to 20% with deionized water, and undissolved impurities were removed by centrifugation, and the supernatant was taken for later use;
[0057] (4) Self-assembly: Add ammonium carbonate solution to a culture dish to form a liquid layer 8 mm deep, add a drop of the modified protein solution 1 cm away from the culture dish, and gently cover the protein solution with a 1 cm × 1 cm polypropylene membrane to ensure that no bubbles are generated. Maintain this state for self-assembly for 1 hour;
[0058] (5) Cleaning and drying: The self-assembled membrane was cleaned with deionized water to remove surface salt and unbound protein solution, and then dried at 20 °C;
[0059] (6) Irradiation treatment: The prepared protein membrane was subjected to electron beam irradiation treatment with an irradiation dose of 100 kGy.
[0060] Example 5
[0061] (1) Impurity removal: Place the bovine serum albumin in a sodium hydroxide solution and boil it at 100° C. for 30 minutes to remove non-cellulose components on the surface, wash the bovine serum albumin with distilled water, and dry it for later use;
[0062] (2) Dissolution and modification: The degummed cellulose is placed in a lithium chloride-dimethyl sulfoxide solution and heated at 75°C for 8 hours to completely dissolve the cellulose and form a uniform protein solution;
[0063] (3) Dilution and purification: The solution in step (2) was diluted to 20% with deionized water, and undissolved impurities were removed by centrifugation, and the supernatant was kept for later use;
[0064] (4) Self-assembly: Sodium phosphate solution was dripped into a culture dish to form a liquid layer 8 mm deep. A drop of the modified protein solution was dripped 1 cm away from the culture dish. A 10 cm × 10 cm polypropylene membrane was gently placed on the protein solution to ensure that no bubbles were generated. This state was maintained for self-assembly for 1.5 hours.
[0065] (5) Cleaning and drying: The self-assembled membrane was cleaned with ethanol to remove surface salt and unbound protein solution, and then dried at 20 °C;
[0066] (6) Irradiation treatment: The prepared protein membrane was subjected to electron beam irradiation treatment with an irradiation dose of 100 kGy.
[0067] Comparative Example 1:
[0068] The irradiation treatment process is replaced by: the absorbed dose is 0 kGy. The remaining parameters are exactly the same as those in Example 2, and the process is also exactly the same.
Claims
1. A method for optimizing the interfacial stability of a protein membrane by electron beam irradiation, wherein the raw materials are composed of a main material, a degumming agent, a dissolving agent, a diluent, a polymer membrane, a self-assembly solution and a cleaning agent, and the mass percentages of the seven components are: main material: 1-5%, degumming agent: 0.2-0.5%, dissolving agent: 10-20%, diluent: 50-70%, self-assembly solution: 3-5%, cleaning agent: 1-5%; wherein, The main material is any one of wool, soy protein, bovine serum albumin, collagen, and silkworm cocoons; the degumming agent is one or two of acetic acid, citric acid, oxalic acid, sodium carbonate, sodium hydroxide, potassium carbonate, potassium hydroxide, and calcium carbonate; the dissolving agent is any one of sodium hydroxide-water solution, sodium phosphate-water solution, potassium hydroxide-ethanol solution, lithium bromide-methanol solution, urea-water solution, calcium chloride-ethanol solution, guanidine hydrochloride-water solution, and lithium chloride-dimethyl sulfoxide solution; the diluent is one or two of sodium chloride solution, phosphate buffer solution, sodium sulfate solution, deionized water, and sodium nitrate solution; the polymer diaphragm is polyethylene, polyvinylidene fluoride, polypropylene, polybenzimidazole, polyether sulfone, polyether ether ketone, fiber any one of element, polyacrylonitrile, polyimide, polypropylene / polyethylene / polypropylene composite membrane; the self-assembly solution is any one of zinc sulfate solution, ammonium carbonate solution, calcium nitrate solution, sodium sulfate solution, calcium chloride solution, potassium nitrate solution, and sodium phosphate solution; the cleaning agent is one or two or three of isopropanol, acetone, ethanol, deionized water, 0.1% acetic acid solution, 0.1% citric acid solution, and 0.1% oxalic acid solution; the seven components are firstly prepared into a protein solution, which is combined with a polymer membrane through self-assembly, and electron beam irradiation treatment is used to induce free radical reactions in protein molecules, promote cross-linking and recombination between molecules, form a stable three-dimensional network structure, and obtain an electron beam irradiation optimized protein membrane.
2. A method for optimizing the interfacial stability of a protein membrane by electron beam irradiation, comprising the following steps: (1) Impurity removal: Place the main material in a degumming agent and boil it at 100°C for 30 minutes to remove surface impurities and non-protein components. Then, wash the main material with distilled water and dry it for later use; (2) Dissolution and modification: The degummed main material is placed in a dissolving agent and heated at 50-80°C for 8-10 hours to completely dissolve the main material and form a uniform protein solution; (3) Dilution and purification: dilute the solution in step (2) to 10%-30% with a diluent, remove undissolved impurities by centrifugation, and take the supernatant for later use; (4) Self-assembly: drip the self-assembly solution into a culture dish to form a liquid layer 8 mm deep, drip a drop of the above protein solution 1-2 cm away from the culture dish, gently cover the protein solution with a polymer membrane of appropriate size to ensure that no bubbles are generated, and maintain this state for self-assembly for 0.5-3 hours; (5) Cleaning and drying: The self-assembled membrane is cleaned with a cleaning agent to remove surface salt and unbound protein solution, and then dried at 16-25°C; Electron beam irradiation treatment: The prepared protein membrane is subjected to electron beam irradiation treatment to further enhance its physical and chemical stability.
3. The method for optimizing the interfacial stability of a protein membrane by electron beam irradiation according to claim 2, characterized in that: The sizes of the polymer membrane in step (4) are 1 cm×1 cm, 3 cm×3 cm, 5 cm×5 cm, 7.5 cm×7.5 cm, and 10 cm×10 cm.
4. The method for optimizing the interfacial stability of a protein membrane by electron beam irradiation according to claim 2, characterized in that: The electron beam irradiation dose in the step (6) is 10-100 kGy.
5. A method for optimizing the interfacial stability of a protein membrane by electron beam irradiation, characterized in that: The protein membrane has excellent physical and chemical stability and can remain stable under adverse conditions such as high temperature and high pressure.
6. A method for optimizing the interfacial stability of a protein membrane by electron beam irradiation, characterized in that: The protein diaphragm electrolyte has good compatibility, and the internal resistance of the prepared lithium battery is reduced and the charge and discharge performance is improved.
7. A method for optimizing the interfacial stability of a protein membrane by electron beam irradiation, characterized in that: The protein diaphragm can effectively reduce the erosion and penetration of the electrolyte to the diaphragm, thereby extending the cycle life of the battery.
8. A method for optimizing the interfacial stability of a protein membrane by electron beam irradiation, characterized in that: Applications in electric vehicles, energy storage systems, portable electronic devices, aerospace, medical devices, military and defense, and renewable energy.
Citation Information
Patent Citations
Method for irradiating and modifying lithium ion battery diaphragm
CN109659473A
A polymer / amyloid-like protein material for inhibiting dendrite growth and a preparation method thereof
CN114335890B